1995
DOI: 10.1143/jjap.34.5706
|View full text |Cite
|
Sign up to set email alerts
|

Application of Lee's Plate Equations to Analysis of Spurious Vibrations of Rectangular AT-Cut Quartz Plates

Abstract: Strip A T-cut quartz resonators have recently been developed and are widely used in frequency applications because of their small size. Many spurious resonances can be supported in a rectangular A T-cut plate. Therefore, analysis of the influence of both the X and Z ′ dimensions of the plate upon the spurious characteristics is necessary to design the strip resonators. However, it is very difficult to exactly solve three-dimensional equations of elasticity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The oscillation mode of rectangular AT-cut quartz resonators has been studied in several works [31][32][33]. It is known with precision that the AT-cut quartz resonator fundamental oscillation mode is in the thickness shear mode, as depicted in figure 6.…”
Section: Probe Dynamics and Sensitivitymentioning
confidence: 99%
“…The oscillation mode of rectangular AT-cut quartz resonators has been studied in several works [31][32][33]. It is known with precision that the AT-cut quartz resonator fundamental oscillation mode is in the thickness shear mode, as depicted in figure 6.…”
Section: Probe Dynamics and Sensitivitymentioning
confidence: 99%
“…3. Figure 4 shows the frequency spectra obtained using the corrected plate equations [3]. The deviation of the spectra calculated from the corrected plate equations is removed from the present results.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…We showed that Lee et al's first order plate equations with two new correction factors predict well in all the spurious frequencies [3]. However, a few discrepancies still remain between calculat,ed and measured data [dl.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation